Optimized parameter of dissimilar joining between Al6061-T6 and height-strength steel with friction stir spot welding process (FSSW) - SILACHAI, Anusak; PRASOMTHONG, Suriya (Journal of Metals, Materials and Minerals, 2022)
High-strength steel and aluminum alloys are used to manufacture modern vehicles. The objective was to reduce the weight and fuel consumption of the vehicles. In this study the optimum parameters for the friction stir spot welding (FSSW) process between Al6061-T6 aluminum alloy and HSS590 high-strength steel were determined. Response surface methodology based on central composite design (CCD) with three parameters, five levels, and 19 runs was used to conduct experiments and develop mathematical regression models. The three joint parameters were tool speed, welding feed, and dwell time. Analysis of variance was then performed to examine the adequacy of the developed models. Finally, the effects of the process parameters on the mechanical properties were investigated using mathematical models. In addition, the distribution of the chemical composition and fracture characteristics of the joints was examined using scanning electron microscopy (SEM). The investigation found that the optimum welding parameters were a tool speed of 1576 rpm, welding feed rate of 45 mm∙min-1, and dwell time of 10 s. Furthermore, the results confirmed that the mathematical models and experiments were consistent.